Synthesis of Functionalized 4-Aryl-2,3 Bis (Trifluoromethanesulfonyloxy) Benzophenones, Based on Site-Selective Suzuki-Miyaura Cross-Coupling Reactions of 2,3,4-Tris (Trifluoromethanesulfonyloxy) Benzophenone. - Eleya, Nadi (Science Journal of University of Zakho, 2013)
Suzuki–Miyaura reactions of the tris(triflate) of 2,3,4-benzophenonewith one 1 equivalent of arylboronic acids afforded 4-aryal-2,3- bis(trifluoromethanesulfonyloxy)benzophenones with very good site selectivity favor of position C4 which is satirically less hindered than position C2.